Plantyclean: Environmentally Friendly Rainwater-Based Drip Irrigation Technology for Water Conservation in Kendari - Zulfaidil Zulfaidil; Wa Ode Tuti Asndari; Shavana Mujahidah Deseree; Clarisa Michelle Pongliling; Keysha Tahta Reisindriya; Oryzasativa Padan’na Ramba (Institut Teknologi Nasional, Bandung, 2026)
AbstrakAir merupakan sumber daya vital yang semakin terancam akibat distribusi tidak merata, pencemaran, dan kerusakan infrastruktur irigasi. Di Kendari, masyarakat masih bergantung pada air hujan dan penyiraman manual, sehingga diperlukan solusi irigasi yang lebih efisien. Penelitian ini memperkenalkan PlantyClean, sistem irigasi tetes berbasis air hujan yang memanfaatkan ember bekas berkapasitas 10 liter, selang plastik berdiameter ½ inci, dan penyangga bambu, yang bekerja menggunakan gaya gravitasi tanpa listrik maupun pompa. Dengan metode eksperimen deskriptif-komparatif, PlantyClean dibandingkan dengan penyiraman manual pada enam tanaman di kebun percobaan SMAN 1 Kendari. Hasil menunjukkan penghematan air hingga ±47% (158 mL/tanaman) dibanding metode konvensional (300 mL/tanaman), dengan debit tetesan rata-rata 0,53 mL/detik (≈1,91 L/jam). Distribusi kelembapan tanah lebih merata, run-off berkurang, dan struktur tanah lebih terjaga. Sebagai sistem pasif, PlantyClean juga berfungsi sebagai media edukatif konservasi air, terbukti efektif, ramah lingkungan, dan berpotensi diterapkan di skala rumah tangga maupun sekolah. Kata kunci: PlantyClean, irigasi tetes, konservasi air, air hujan, teknologi ramah lingkungan. AbstractWater is a vital resource increasingly threatened by uneven distribution, pollution, and damaged irrigation infrastructure. In Kendari, communities still rely heavily on rainwater and manual watering, necessitating more efficient irrigation solutions. This study introduces PlantyClean, a simple rainwater-based drip irrigation system utilizing a 10-liter recycled bucket, ½-inch plastic tubing, and bamboo supports, operating purely by gravity without electricity or pumps. Using a descriptive-comparative experimental method, PlantyClean was compared against manual watering on six plants at SMAN 1 Kendari's experimental garden. Results showed PlantyClean reduced water consumption by approximately 47% (158 mL/plant) compared to conventional watering (300 mL/plant), with an average drip rate of 0.53 mL/s (≈1.91 L/hour). Soil moisture distribution was more uniform, runoff was minimized, and soil structure was better preserved. As a passive system requiring no manual labor, PlantyClean also serves as an educational tool for water conservation awareness, proving effective, eco-friendly, and scalable for household and school settings. Keywords: PlantyClean, drip irrigation, water conservation, rainwater, environmentally friendly technology